BAHA Skin Complications in the Pediatric Population: Systematic Review With Meta-analysis. Issue 7 (August 2018) - Shapiro, Scott; Ramadan, Jad; Cassis, Adam
Abstract : Objective: Compare the incidence of skin and surgical site complications for children undergoing percutaneous and transcutaneous bone conduction implant (pBCI and tBCI) surgery via systematic review and meta-analysis of the available data. Data Sources: 1) Search of PubMed, Web of Science, and EBSCOhost databases from January 2012 to April 2017. 2) References of studies meeting initial criteria. Study Selection: Inclusion criteria were studies that involved patients less than 18 years old undergoing tBCI or pBCI surgery with a BI300 implant and reported skin complications, implant loss, and need for revision surgery. Exclusion criterion was use of a previous generation implant. Data Extraction: Implants used, number of patients, age, surgical technique, Holgers score, incidence of skin complication, implant loss, and reoperation. Bias assessment performed with the Newcastle–Ottawa Scale. Data Synthesis: Twenty-two studies (14 tBCI, 8 pBCI) met criteria. Meta-analysis was performed using a random effects model. Cochran's Q score and I 2 inconsistency were used to assess for heterogeneity. Overall estimated skin complication rate for tBCIs was 6.3% versus 30% for pBCIs ( p = 4 × 10 −12 ). Implant loss was 0% for tBCIs and 5.3% for pBCIs ( p = 0.004). Reoperation rate was 3.0% and 6.2% for tBCIs and pBCIs respectively ( p = 0.00002). Conclusion: There is strong evidence to suggest that in pediatric patients, the incidence of skin complications, implant loss, and rate of reoperation are higher for pBCIs compared with tBCIs. This information should be part of any discussion about BCI surgery on a pediatric patient. Abstract : Supplemental Digital Content is available in the text